Evaluation of Four Commonly Used DNA Barcoding Loci for Ardisia Species Identification - Xiong, Chao; Sun, Wei; Wu, Lan; Xu, Ran; Zhang, Yancheng; Zhu, Wenjun; J., H. E.; Panjwani,; Liu, Zhiguo; Zhao, Bo (Frontiers in Plant Science, 2022)
Ardisia plants have been used as medicinal plants for a long time in China. Traditional techniques such as morphological, microscopic, and chemical identification methods all have limitations in the species identification of Ardisia. For the sake of drug safety, four DNA barcodes (psbA-trnH, ITS, rbcL, matK) were assessed for Ardisia plants using a total of 121 individuals from 34 species. Four criteria (The success rates of PCR amplification, DNA barcoding gap, DNA sequence similarity analysis and NJ tree clustering analysis) were used to evaluate the species identification ability of these four DNA barcodes. The results show that ITS had the highest efficiency in terms of PCR and sequencing and exhibited the most apparent inter- and intra-specific divergences and the highest species identification efficiency. There was no significant increase in species identification after combining the three cpDNA fragments with the ITS fragment. Considering the cost and experimental effectiveness, we recommend ITS as the core barcode for identifying Ardisia plants.